Mutualism and health care : Hospital contributory schemes in twentieth-century Britain. - Gorsky, Martin (Manchester University Press, 2006)
Mutualism and health care presents the first comprehensive account of a major innovation in hospital funding before the NHS. The voluntary hospitals, which provided the bulk of Britain?s acute hospital services, diversified their financial base by establishing hospital contributory schemes. Through these, working people subscribed small, regular amounts to their local hospitals, in return for which they were eligible for free hospital care. Mutualism and health care evaluates the extent to which the schemes were successful in achieving comprehensive coverage of the population, funding hospital.